2020
DOI: 10.1186/s12902-020-0511-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of leptin and adiponectin with incident type 2 diabetes and interactions among African Americans: the Jackson heart study

Abstract: Background: Growing evidence suggests that leptin is critical for glycemic control. Impaired leptin signaling may also contribute to low adiponectin expression in obese individuals. We assessed the association of leptin and adiponectin with incident type 2 diabetes (T2D), their interactions with sex and obesity status, and mediation by insulin resistance. Methods: We included study participants from the Jackson Heart Study, a prospective cohort of adult African Americans in Jackson, Mississippi, that were free… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
3
17
1
Order By: Relevance
“…In thepresent study, the mean age for cases was 42.98±8.16 years and controls was 36.75±5.84 years which was in accordance with a study done by Diwan et al 12 The present study revealed that mean BMI for control group was 22.56±4.13 and T2DM(Study group) was 25.85±4.34. These findings were similar to the study reported by Lalrindiki et al 13 Present study reports that mean Waist Circumference (WC) in T2DM group were more i.e 99.51±3.65 cm than in control group i.e 86.74±8.09 cm which was in accordance to the study reported by Aurelian Bidulescu et al 14 and contradictory to the study done by Lalrindiki et al 13 Similarly our study revealed that mean waist hip ratio (WHR) were increased in T2DM group than in control group which is almost similar to the findings of Lalrindiki et al 13 Increased Waist circumference (WC) and Waist hip ratio (WHR) in T2DM group could be attributed to the fact that such individuals may have accumulated fat levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In thepresent study, the mean age for cases was 42.98±8.16 years and controls was 36.75±5.84 years which was in accordance with a study done by Diwan et al 12 The present study revealed that mean BMI for control group was 22.56±4.13 and T2DM(Study group) was 25.85±4.34. These findings were similar to the study reported by Lalrindiki et al 13 Present study reports that mean Waist Circumference (WC) in T2DM group were more i.e 99.51±3.65 cm than in control group i.e 86.74±8.09 cm which was in accordance to the study reported by Aurelian Bidulescu et al 14 and contradictory to the study done by Lalrindiki et al 13 Similarly our study revealed that mean waist hip ratio (WHR) were increased in T2DM group than in control group which is almost similar to the findings of Lalrindiki et al 13 Increased Waist circumference (WC) and Waist hip ratio (WHR) in T2DM group could be attributed to the fact that such individuals may have accumulated fat levels.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly our study results revealed that serum insulin and HOMA-IR were increased in T2DM. These findings were similar to the study reported by Aurelian Bidulescu et al 14 Present study results highlights that Adiponectin is positively correlated with HDL, TC, and LDL while other anthropometric indices markers of insulin resistance and Triglycerides had negative correlation which is in accordance with the study reported by Prema Adhikari et al 15 Similarly, leptin is negatively correlated with HDL while other anthropometric indices markers of insulin resistance and Triglycerides had positive correlation similar to the study reported by Amita yadav et al 16…”
Section: Discussionsupporting
confidence: 92%
“…In order to evaluate the possibility of confounding by BMI, we fit models testing the association of leptin and incident T2D without adjustment TA B L E 2 Cox proportional hazards regression models testing the association of adiposity-related biomarkers with progression to T2D per 1-SD increase in each biomarker, overall and stratified by history of GDM for BMI and found an HR for T2D of 1.179 (p < 0.001) and 0.880 (p = 0.093) for a 1-SD change in women without and with a history of GDM, respectively, compared with a BMI-adjusted HR of 1.126 (p = 0.016) and 0.776 (p = 0.013), suggesting that confounding by BMI did not explain the difference in associations of leptin with T2D risk that we observed in women without and with a history of GDM. Differences in age across the cohorts are also unlikely to explain differences in the observed association of leptin with T2D risk, as average age was similar among the previous reports (ranging from 52 to 56 years among studies reporting a mean value for age) (28)(29)(30)32). Another possibility is menopausal status.…”
Section: Higher Circulating Leptin Levels Have Previously Been Associatedmentioning
confidence: 50%
“…with increased risk of incident T2D or worsening hyperinsulinemia, independent of BMI or adiposity in large longitudinal cohorts (28)(29)(30). In the Jackson Heart Study, a longitudinal cohort of Black participants (n = 3,363), higher circulating leptin levels were associated with higher odds of T2D over 7 years, independent of BMI, overall and among male participants only (HR for 1-unit increase in log leptin level in ng/mL overall = 1.3 [95% CI: 1.1-1.6]; in men…”
Section: Higher Circulating Leptin Levels Have Previously Been Associatedmentioning
confidence: 96%
“…Evidence shows that leptin is involved in glucose metabolism, innate immune reactions and acute inflammation. The concentration of leptin in blood in obese patients with dyslipidemia is high, causing signaling alteration, promoting the development of insulin resistance and T2D [92,93]. In mice, it has been described an increase in leptin is associated with inflammatory markers in obese individuals [94], and in humans production of cytokines can be induce when leptin is administered exogenously [95].…”
Section: Immune Alterations In Obesity and T2dmentioning
confidence: 99%